The Role of Interleukin-10 in Women with Metastatic Invasive Ductal Carcinoma - Althwani, Amina N.; Najm, Mohammed A. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Breast cancer is the malignant tumor that forms from the uncontrolled growth of abnormal breast cells. It usually affects tissues involved in milk production (Ductal and lobular tissues). It is the most common malignancy in women and it remains one of the greatest health threats facing women around the world as we enter the 21st century.Objectives: To estimate the role of IL-10 in the progression of invasive ductal carcinoma.Patients and Method: Seventy three metastatic invasive ductal carcinoma Iraqi women were admitted to Nuclear Medicine Hospital in Baghdad and 15 samples of apparently healthy women were involved as a control. The blood samples (2 mL) were drown from all studied cases in order to be used for measuring their serum level of IL-10 by using Enzyme-linked Immune Sorbent Assay technique.Result: The results have shown that the high significant relation was that of elevated IL-10 levels, which increased in 98.6% of patients.Conclusion: The result indicates that the highl significant elevation of serum IL-10 concentration are strongly associated with metastatic invasive ductal carcinoma, this may be helpful in adding further vision in the diagnosis of women with this type of cancer.